2008
DOI: 10.1007/s10529-008-9811-5
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of OsDREB genes lead to enhanced drought tolerance in rice

Abstract: The DREB transcription factors, which specifically interact with C-repeat/DRE (A/GCCGAC), play an important role in plant abiotic stress tolerance by controlling the expression of many cold or/and drought-inducible genes in an ABA-independent pathway. We have isolated three novel rice DREB genes, OsDREB1E, OsDREB1G, and OsDREB2B, which are homologous to Arabidopsis DREB genes. The yeast one-hybrid assay indicated that OsDREB1E, OsDREB1G, and OsDREB2B can specifically bind to the C-repeat/DRE element. To elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(158 citation statements)
references
References 26 publications
2
155
0
1
Order By: Relevance
“…DREB1/CBF encodes group IIIc AP2/ERFs, which regulate expression of genes associated with tolerance to drought, salinity, and low temperature in Arabidopsis and rice (Nakashima et al, 2009). It has been reported that overexpression of rice DREB1A and DREB1E significantly increases survival of water deficit (Ito et al, 2006;Chen et al, 2008). We found that drought stress induced the accumulation of DREB1A mRNA in aerial tissue of M202 and M202(Sub1), but the level was significantly higher in M202 (Sub1) at days 3 and 4 ( Figure 2).…”
Section: Sub1a Upregulates Genes Involved In Acclimation To Droughtmentioning
confidence: 99%
“…DREB1/CBF encodes group IIIc AP2/ERFs, which regulate expression of genes associated with tolerance to drought, salinity, and low temperature in Arabidopsis and rice (Nakashima et al, 2009). It has been reported that overexpression of rice DREB1A and DREB1E significantly increases survival of water deficit (Ito et al, 2006;Chen et al, 2008). We found that drought stress induced the accumulation of DREB1A mRNA in aerial tissue of M202 and M202(Sub1), but the level was significantly higher in M202 (Sub1) at days 3 and 4 ( Figure 2).…”
Section: Sub1a Upregulates Genes Involved In Acclimation To Droughtmentioning
confidence: 99%
“…Overexpression of DREB1A improves cold-and dehydration-stress tolerance, while DREB2ACA improves dehydration tolerance and only slightly cold tolerance in transgenic plants (Nakashima et al, 2014). In contrast with these results, constitutive ectopic expression, or stress-induced expression of maize ZmDREB2A (Qin et al, 2008) and soybean GmDREB2 (Chen et al, 2008) in Arabidopsis results in better drought, heat and salt stress tolerance in transgenic plants, without growth defects. This suggests that ZmDREB2A and GmDREB2 do not require modification (Yang et al, 2010).…”
Section: Selected Drought Tolerance Genesmentioning
confidence: 79%
“…In our previous study, overexpression of FvMYB1 mainly induced the upregulation of some stress-related genes, such as SOD, P5CS, and DREB . Among them, most DREB genes have been identified to play roles in an ABA-independent way under stress (Chen et al, 2008), and so we suspected that FvMYB1 enhanced salt stress tolerance mainly through the ABAindependent way. Here, ectopic expression of FvMYB2 increased the expression of stress-related genes NtERD10C and NtRD29A, which or whose homologues have been reported to play important roles in preventing water loss in cells; overexpression of these genes conferred stress tolerance (Huo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%